Digital Competence of Rural Teachers in Depopulated Regions of Spain: A Bibliometric Review - Pablo Fernández-Arias; María Sánchez-Jiménez; Álvaro Antón-Sancho; María Nieto-Sobrino; Diego Vergara (European Journal of Investigation in Health, Psychology and Education)
Rural teachers have the potential to be important agents of local development. To achieve this goal, they need to acquire high digital competence in order to effectively integrate technology into their pedagogical practices, thus enriching the learning experience of students and fostering their participation. Digital competence contributes to reducing the education gap between urban and rural areas, promoting educational equity and inclusion. High digital competence also enables rural teachers to address the specific challenges of their environment, such as cultural diversity, scarce resources, and low population density. Against this backdrop, this article presents a bibliometric review of the importance of digital competence in rural teachers in Spain, where the problem of rural depopulation, as in other regions of Europe, has been accentuated in recent years. The objective of the bibliometric review is both (i) to find the strengths and weaknesses that concern researchers in relation to the digital training of teachers in rural areas and (ii) to express them explicitly in order to contribute to propose solutions. The results reveal the growing academic and political attention being paid to this issue, highlighting the need for rural teachers to acquire digital skills to adapt to current educational demands. In addition, they point to the importance of developing specific policies and programs in Europe as well as providing training opportunities and ongoing support to ensure that teachers in rural contexts can acquire or strengthen their digital competence, thereby improving the quality of education in these areas.